Perspectives of EFL learners and teachers on self-efficacy and academic achievement: The role of gender, culture and learning environment - Liu, Liyuan; Saeed, Muhammad Amir; Abdelrasheed, Nasser Said Gomaa; Shakibaei, Goodarz; Khafaga, Ayman Farid (Frontiers in Psychology, 2022)
The Omani socio-cultural context, the mono-gender educational system in schools, and the learning environment at the higher educational institutions significantly affect learners' self-efficacy and academic achievement in the mixed-gender EFL classroom. Different studies have revealed both positive and negative implications of mixed-gender classrooms, especially for those who came from a mono-gender learning environment. The adjustment phase for the tertiary learners from school to the university is not only crucial but also significant for the continuation of higher education. The effects of socio-cultural factors on self-efficacy and academic achievement have not been studied in depth, particularly in eastern countries. So, the current study aimed at investigating the role of gender, learning background, socio-cultural circumstances, and the effect of the learning environment on EFL learners' self-efficacy and their academic achievement within the scenario of the prevailing culture and traditions in the Dhofar Region. To conduct this study, mixed research methods (qualitative and quantitative) have been adopted to investigate the perceptions of both teachers and learners. The sample of the study consists of 117 EFL learners ranging between 18–22 years of age and 25 EFL teachers ranging between 35–60 years of age. We used separate surveys for students and the teachers and interviewed students and teachers on a random basis. The results demonstrate that both genders were comfortable in segregated classes. The results also reveal that female learners were active learners and better performers than male learners in the school learning environment. The students reported that social restrictions discouraged them from mixing with the opposite gender in classroom activities and oral discussions. Most teachers believe that, compared to male learners, female learners performed better and were more engaged and responsive to different learning situations. The study found that there were statistically significant differences between both genders in terms of the effects of socio-cultural environment, self-efficacy, and the learning environment. Female learners were better than male learners in mono-gender schools, and they have higher self-efficacy than male students at the university. In conclusion, EFL teachers should consider the socio-cultural context, learners' learning background, and other challenges of learners to bring out positive outcomes in a mixed-gender classroom.